Tryptanthrin Analogues as Inhibitors of Enoyl-acyl Carrier Protein Reductase: Activity against Mycobacterium tuberculosis, Toxicity, Modeling of Enzyme Binding - Duca, Gheorghe; Pogrebnoi, Serghei; Boldescu, Veaceslav; Aksakal, Fatma; Uncu, Andrei; Valica, Vladimir; Uncu, Livia; Negres, Simona; Nicolescu, Florica; Macaev, Fliur (Current Topics in Medicinal Chemistry, 2019)
Background: High numbers of infection with resistant forms of Micobacterium tuberculosis (Mtb) contribute to a constant growing demand in new highly active and effective therapeutics. Current drug discovery efforts directed towards new antituberculosis agents include the development of new inhibitors of enoyl-acyl carrier protein reductase (InhA) that do not require activation by the specific enzymes. Tryptanthrin is a known inhibitor of Mtb InhA and its analogues are investigated as potential agents with antimycobacterial efficiency. Objective: The main objective of the presented research was to develop a new group of tryptanthrin analogues with good inhibition properties against Mtb. Methods: Synthesis of new derivatives of 5H-[1,3,4]thiadiazolo[2,3- b]quinazolin-5-one and evaluation of their activity against Mtb, as well as acute and chronic toxicity studies were carried out. Molecular modeling studies were performed to investigate the binding mechanisms of the synthesized ligands with InhA. Binding energies and non-covalent interactions stabilizing the ligand-receptor complexes were obtained from the results of molecular docking. Results: The most active compound in the obtained series, 2-(propylthio)-5H-[1,3,4]thiadiazolo[2,3- b]quinazolin-5-one, exhibited the superior inhibition activity (up to 100%) against mycobacterial growth at MIC 6.5 μg/mL, showed good affinity to the InhA enzyme in docking studies and demonstrated a very low per oral toxicity in animals falling under the category 5 according to GHS classification. Conclusion: 2-(propylthio)-5H-[1,3,4]thiadiazolo[2,3-b]quinazolin-5-one can be further explored for the development of a new series of compounds active against Mtb.
Keywords: Enoyl-acyl carrier protein reductase